The adventures of Tintin [videorecording (DVD)] - Spielberg, Steven, 1946-; Bell, Jamie, 1986-; Serkis, Andy; Craig, Daniel, 1968-; Hergé, 1907-1983 (Paramount Pictures, 2012)
Racing to uncover the secrets of a sunken ship that may hold a vast fortune -- but also an ancient curse -- Tintin and his loyal dog Snowy embark on an action-packed journey.